2023
DOI: 10.46827/ejes.v10i11.5063
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Confidence of Classroom Assessment Practices: A Case of Basic Schools in Upper Denkyira West District, Ghana

Samuel Oppong,
Regina Mawusi Nugba,
Eugene Asamoah
et al.

Abstract: Teachers' confidence in classroom activities has been a major concern for educators and major stakeholders in Ghana. However, the literature suggests that showing higher confidence in classroom practices positively impact students learning outcome. The specific purposes of the study were to determine whether teachers are confident in (1) monitoring, analysing, and communicating assessment results and (2) assessment, design, implementation, and feedback. The study also sought to find out whether gender plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Reportedly, primary school teachers are generally more optimistic about their ability to implement the various classroom assessment strategies. The study by Oppong et al (2023) found that teachers have a high level of confidence in their classroom assessment practices. It also revealed no significant gender differences in teachers' confidence in implementing classroom assessment.…”
Section: Self-efficacy In Classroom Assessmentmentioning
confidence: 99%
“…Reportedly, primary school teachers are generally more optimistic about their ability to implement the various classroom assessment strategies. The study by Oppong et al (2023) found that teachers have a high level of confidence in their classroom assessment practices. It also revealed no significant gender differences in teachers' confidence in implementing classroom assessment.…”
Section: Self-efficacy In Classroom Assessmentmentioning
confidence: 99%